Beyond the Dual Year?: The last Decade of Spain-Russia Relations - Morales, Javier (UNISCI Discussion Papers, 2011)
This article presents the evolution of Spanish-Russian relations since 2000, which we can divide into three stages according to the changes of government in Spain – with the Socialist Party’s victory in 2004 – and Russia, after Medvedev came to power in 2008. We start with a brief historical overview, and then we continue with an analysis of the political, security, economic and cultural aspects of the bilateral contacts. Finally, in our conclusions we make an attempt at conceptually defining the main features of this relationship.
Keywords: Spain; Russia; bilateral relations; Dual Year.